Multi-omics interpretation of how lysophospholipids regulate hepatic lipid metabolism and immunity in hybrid grouper (♀Epinephelus fuscoguttatus × ♂Epinephelus Lanceolatu) fed high-lipid diets - Hongjin Deng; Jiacheng Zhang; Weixing Liang; Beiping Tan; Shuyan Chi (Animal Nutrition)
This experiment explored the effects of lysophospholipids on hybrid grouper (initial average weight: 22.65 ± 0.03 g) hepatic lipid metabolism and immunity at the transcriptome and metabolome levels. A total of 375 hybrid groupers were divided into 5 groups of 3 replicates of 25 fish each. Five isoproteic and isolipidic diets were formed by adding 0 (L0, control group), 0.05% (L0.05), 0.1% (L0.1), 0.15% (L0.15) and 0.2% (L0.2) lysophospholipids, respectively. After 8 wk, compared to the control group, weight gain rate, specific growth rate and protein deposition rate were significantly higher (P < 0.05), and the feed conversion ratio was significantly lower in the L0.1 group (P = 0.011). The total cholesterol and triglyceride contents in the serum and liver of the fish in the L0.1 group were significantly lower than those in the L0 group (P < 0.05). Compared to the L0 group, catalase and superoxide dismutase activities were substantially higher, and malondialdehyde content was considerably lower in the L0.1 group (P < 0.05); complement 3, lysozyme, acid phosphatase, and alkaline phosphatase levels in the L0.1 group were significantly higher than those in the L0 group (P < 0.05). The hepatic lipoprotein lipase activity and gene expression in the L0.1 group were significantly higher whereas fatty acid synthase activity and gene expression were significantly lower than those in the L0 group (P < 0.05). The gene expression and activities of hepatic catalase and superoxide dismutase in the L0.1 group were considerably higher than those in the control group (P < 0.05). The mRNA expression of major histocompatibility complex class II molecule and interleukin-10 genes were significantly higher in the L0.1 group than in the L0 group (P < 0.05), while the mRNA expression of interleukin-6 and interferon-γ genes in the L0 group was significantly higher than those in the L0.1 group (P < 0.05).The transcriptome and metabolome data showed that the critical genes such as lipoprotein lipase and fatty acid synthase, as well as metabolites such as taurine and docosahexaenoic acid were enriched in the lipid metabolism pathway. In conclusion, 0.1% lysophospholipids activated critical genes and metabolites in the adenosine 5-monophosphate-activated protein kinase and peroxisome proliferators-activated receptors signaling pathways to regulate lipid metabolism and immunity in hybrid grouper.